Psychosocial Underpinnings of Pain and Sleep Disturbance in Safety-Net Primary Care Patients. (29th April 2020) - Griffin, Sarah; Tan, Joseph; Perrin, Paul B.; Williams, Allison B.; Smith, Erin R.; Rybarczyk, Bruce
Abstract : Objective . The aim of this study was to uncover possible psychosocial underpinnings of pain and sleep disturbance in a safety-net primary care sample. Methods . Patients ( n = 210) awaiting care in a safety-net primary care clinic waiting room completed measures of cynical hostility, social support, mental health, sleep disturbance, and pain. This study was cross-sectional and observational. Results . A structural equation model suggested that higher cynical hostility was associated with lower social support, which in turn was associated with poorer mental health, which then corresponded with higher pain and sleep disturbance. All possible indirect (mediational) effects within this model were statistically significant, suggesting a possible route through which cynical hostility may shape pain and sleep, two common presenting problems in primary care. Conclusions . These findings illustrate the interplay of psychosocial factors with chronic pain and sleep disturbance in a sample of low-income, predominantly African-American patients seeking care at a safety-net primary care clinic. The findings support integrated primary care as a way to target not only behavioral health issues but also the psychosocial factors entangled with physical health.